2013
DOI: 10.2147/ceor.s34321
|View full text |Cite
|
Sign up to set email alerts
|

The clinical and economic burden of chronic obstructive pulmonary disease in the USA

Abstract: Chronic obstructive pulmonary disease (COPD) is the third most common cause of death in the USA. In 2010, the cost of COPD in the USA was projected to be approximately US$50 billion, which includes $20 billion in indirect costs and $30 billion in direct health care expenditures. These costs can be expected to continue to rise with this progressive disease. Costs increase with increasing severity of disease, and hospital stays account for the majority of these costs. Patients are diagnosed with COPD following a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
157
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(175 citation statements)
references
References 72 publications
2
157
0
2
Order By: Relevance
“…It is the third most common cause of death in the USA. It is estimated that the healthcare-related cost for COPD was approximately US$50 billion in 2010(1). These costs can be expected to continue to rise with this progressive disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is the third most common cause of death in the USA. It is estimated that the healthcare-related cost for COPD was approximately US$50 billion in 2010(1). These costs can be expected to continue to rise with this progressive disease.…”
Section: Introductionmentioning
confidence: 99%
“…These costs can be expected to continue to rise with this progressive disease. Costs increase with increasing severity of disease, and hospital stays account for the majority of these costs(1). …”
Section: Introductionmentioning
confidence: 99%
“…COPD is a disease associated with substantial economic burden worldwide 5,6. Previous studies conducted in China showed that COPD was also costly and imposed an enormous economic burden on both families and society in the country.…”
Section: Introductionmentioning
confidence: 99%
“…With increasing prevalence, the economic burden of COPD is also increasing. In 2010, the estimated cost of COPD in the USA was $50 billion, which included $20 billion of indirect costs and $30 billion of direct health care expenditures 2. Although more studies have recently investigated the economic burden of COPD, existing data show remarkable variations due to differences in survey methods, diagnostic criteria, and analytic approaches 3.…”
Section: Introductionmentioning
confidence: 99%